The relationship between polysubstance abuse and myocardial histopathological lesions - Thuong, Do Thi Thuong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Background: Substance abuse can affect most organs of the body, with the cardiovascular system being a primary target. Objective: This study aims to investigate the association between myocardial lesions and polysubstance use status. Subjects and Methods: Subjects and Methods: A total of fifty-five deceased individuals were examined at the Ho Chi Minh City Forensic Medicine Center, all of whom tested positive for substance abuse through blood tests. Myocardial injuries were assessed using Hematoxylin and Eosin (HE) and Trichrome Masson histopathology specimens. Results: The study found that all cases (100%) involved morphine use, with 65.5% involving the concurrent use of two substances and 7.3% involving the concurrent use of three substances. The most common myocardial lesions observed were fibrotic proliferation (72.7%) and ischemia-related lesions (34.5%). Conclusion: The study demonstrates a significant association between polysubstance abuse and the risk of fibrogenesis and fat infiltration in the myocardium. These findings underscore the importance of addressing polysubstance abuse in cardiovascular health interventions.